The influence of nutritional factors on prostate cancer incidence and aggressiveness. (2nd January 2018) - Pascual-Geler, Manrique; Urquiza-Salvat, Noelia; Cozar, Jose Manuel; Robles-Fernandez, Inmaculada; Rivas, Ana; Martinez-Gonzalez, Luis Javier; Ocaña-Peinado, Francisco Manuel; Lorente, Jose Antonio; Alvarez-Cubero, Maria Jesus
Abstract: There is an increasing evidence for a link between nutrition, lifestyle and prostate cancer (PCa) development and/or progression of disease. The objective of this study was to examine the association between dietary factors and PCa incidence and aggressiveness in a case-control study. After the analysis of the anatomic pathology, subjects were classified in patients with PCa ( n  = 157) and controls ( n  = 158). Clinical data including Gleason score, PSA values and biopsy results, were compiled. Frequencies of food consumption and sociodemographic data were also obtained. The results showed that physical activity was significantly higher in control ( p  < .022). It was also found that some nutritional habits offer a protective effect among studied subjects, like high nuts ( p  = .041) and fish ( p  = .041) intakes. Moreover, there was a significant reduction in risk ( p  = .029) in cases with a higher fruits and vegetables intakes. A decreased risk of aggressive PCa was associated with fruits, vegetables, legumes and fish intakes. However, these relationships were not statistically significant when data were adjusted for covariates. In conclusion, this study found an inverse association between PCa risk and the intake of fruits and vegetables, fish and nuts. The results suggested that a diet with higher intakes of these foods as Mediterranean diet may lower the risk of PCa in the studied population. As dietary factors are modifiable, identifying food groups or dietary patterns that modulate the risk of PCa and its aggressiveness can offer effective and practical strategies for its primary prevention.